The effect of logistic service quality on customer satisfaction and loyalty using kansei engineering during the COVID-19 pandemic - Dian Palupi Restuputri; Tri Ratna Indriani; Ilyas Masudin (Cogent Business & Management, 2021)
This article identifies the influence of logistics service quality in Indonesia on customer satisfaction and loyalty during the COVID-19 pandemic and customer trust as a moderating variable. In this study, the service quality consists of three variables: the quality of staff service, quality of operational service, and technical service quality. In this study, a conceptual model was generated by providing four other variables: customer satisfaction, customer trust, customer loyalty, and customer commitment. The 300 respondents were selected to fill out the formal questionnaire, while 30 respondents were as a trial for the formal questionnaire. The questionnaire trial analysis was assisted by SPSS 23, while the formal questionnaire analysis was carried out with SmartPLS 3.0. This study resulted in four hypotheses accepted from the ten proposed hypotheses. The results show that the quality of staff service and technical service quality significantly affects customer satisfaction. It is also found that customer satisfaction and customer trust have a significant effect on customer loyalty. The use of Kansei in this study will provide a different perspective to describe customer services during the COVID-19 pandemic.
Keywords: 650; Logistics services quality; COVID-19 pandemic; Kansei engineering; customer trust; customer loyalty; customer satisfaction